The Effectiveness of a Proposed Educational Unit for Training on the Wilcom Program in the Machine Embroidery Technology Course - Alzayla'aee, Amani Abdu Ahmad; Alzahrani, Kherah Award (Journal of Humanities & Social Sciences, 2023)
This study aimed to prepare a training program as a proposed educational unit in developing the machine embroidery technology course within the fourth-level courses for the students of the Fashion Design Department at the College of Designs and Arts. The objective was to identify the program’s effectiveness and measure its impact on the development of the knowledge and skill side of the students through the proposed training program. The researchers used the experimental method to measure the effectiveness of the Wilcom machine embroidery program in training female students, developing their technical and skillful performance, and increasing their experience in designing decorative embroidery units of high value, which helps in developing the machine embroidery technology course, and the descriptive approach in describing and explaining the Wilcom program and describing and formulating the training program in an educational unit that includes specific lessons suggested in the machine embroidery technology course. The research tools included an assessment form for specialized experts to measure the effectiveness of the training program, a cognitive achievement test (pre and post) to measure the cognitive aspect of the proposed educational unit, an applied test (pre and post) to measure skill performance on the proposed educational unit, a skill performance assessment scale, and a questionnaire to measure the attitude of female students towards learning the proposed educational unit. The training program was applied to an intentional sample chosen according to specific criteria that serve the researchers and achieve the purpose of the study they are conducting. The sample included an entire class consisting of 14 students from the fourth-level fashion design department enrolled in the machine embroidery technology course. The results proved the effectiveness of the proposed educational unit in developing the course using computer technologies, which was evident in increasing the student’s ability to develop the knowledge achievement associated with the Wilcom program.